Analisis Peluang Pasar Suplemen Tulang Berbahan Aktif Tanaman Lokal di Jawa Tengah - Putri, Khairina Rahmania Prayoga; Setiawati, Indah; Istiqomah, Vina Helmi Nur; Maspudah, Ai Munawaroh Sa’adatul; Nuraini, Linda Aulia; Alexsyah, Fakhri Dwi (Universitas Galuh, 2024)
The research was conducted to determine the market aspects of innovative bone supplement products in the form of effervescent tablets that utilize local plant from Central Java by analyzing interest, competitors, and business potential. The research method was carried out using the method of literature study and development strategy. The data obtained was sourced from Google Trends for information on the level of product interest. A data search through Google was conducted to find competitor information in the market. The analysis was conducted using interest analysis using Google Trends, SWOT analysis, and competitor analysis. The results showed that this supplement product has a great opportunity and is able to compete with other products to sell in the market of Central Java Province, because the supplements presented have many advantages compared to other similar products in terms of price, content, and target consumers.